THE ROLE AND SIGNIFICANCE OF THE TURKISTAN SUMMIT IN THE ACTIVITIES OF THE ORGANIZATION OF TURKIC STATES - Murtazayeva, Sh. M. (Oriental Journal of History, Politics and Law, 2026)
This article analyzes the role and significance of the Turkistan Summit within the framework of the Organization of Turkic States. The study examines the impact of the summit on the political and economic strategies of member states, as well as its role in strengthening mutual trust and regional integration. Furthermore, it explores the distinctive features of the Turkistan Summit, Uzbekistan’s position and initiatives within this process, and analyzes the proposals put forward regarding the priority areas of cooperation among the member states.